Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1990
DOI: 10.1172/jci114878
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis of hyperadrenergic orthostatic hypotension. Evidence of disordered venous innervation exclusively in the lower limbs.

Abstract: The pathogenesis of hyperadrenergic orthostatic hypotension was studied in eight patients. Correction of the abnormal orthostatic changes by an inflated pressure suit (MAST) confirmed previous evidence of excessive gravitational

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
82
2
2

Year Published

1992
1992
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(92 citation statements)
references
References 19 publications
(7 reference statements)
5
82
2
2
Order By: Relevance
“…On the one hand, these results can be interpreted as being consistent with hypotheses regarding the origins of POTS involving distal extremity denervation, or the so-called "long tract syndrome" (4,19), in which peripheral nerve deficit is confined to the legs. On the other hand, our results suggest a more widespread loss of vasoconstrictor tone involving both arm and leg.…”
Section: Discussionsupporting
confidence: 84%
“…On the one hand, these results can be interpreted as being consistent with hypotheses regarding the origins of POTS involving distal extremity denervation, or the so-called "long tract syndrome" (4,19), in which peripheral nerve deficit is confined to the legs. On the other hand, our results suggest a more widespread loss of vasoconstrictor tone involving both arm and leg.…”
Section: Discussionsupporting
confidence: 84%
“…Venous pooling occurs in the lower limbs as the heart rate increases during the HUTT. 6,7,11 Because similar mechanisms are involved in vitamin B 12 deficiency, we believe that patients with CFS, POTS, and syncope should be screened for vitamin B 12 deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…9,10 Neurally mediated hypotension has been shown to be the most common cause of unexplained recurrent syncope, and overlapping findings have been found in CFS and neurally mediated hypotension. 9 When defining hyperadrenergic orthostatic hypotension with increased plasma levels of epinephrine and norepinephrine, Streeten 11 found that orthostatic hypotension developed due to the accumulation of blood resulting from anatomic or functional postganglionic denervation in the lower-limb veins.…”
mentioning
confidence: 99%
“…This compensatory mechanismwasnot seen in the patient. Although Streeten and Scullard stressed that the disordered venous innervation exists exclusively in the lower limbs in patients with hyperadrenergic orthostatic hypotension (6,9), the present case could have generalized adrenergic denervation because the decreased sweat response to iontophoresis of acetylcholine was seen in both upper limbs and lower limbs. Another characteristic finding of this patient was an excessive blood pressure elevation in the phase IV of the Valsalva maneuver.…”
mentioning
confidence: 53%